Knowledge and Practices among Dental Practitioners Regarding the Use of Antimicrobials for Periodontal Diseases: An Online Survey in Saudi Arabia - Mohammed Sultan Al-Ak'hali; Esam Halboub; Mona Awad Kamil; Wafa Hassan Alaajam; Abdulaziz Mahnashi; Jabbar Khubrani; Abdullah Mahnashi; Khalid Mahnashi; Nuha Farea (MDPI AG, 2023)
This study aimed to investigate the knowledge and practices among dental practitioners in Saudi Arabia regarding the use of antimicrobials for periodontal diseases. An online questionnaire was sent to senior dental students and dental practitioners including interns, general dental practitioners (GDP), and periodontists in Saudi Arabia. Two hundred and twenty-three dental practitioners responded and participated in the study. The potential associations between the use of antimicrobials and different variables were assessed by a chi-square test. The majority of the participants (84.3%) reported prescribing systemic antimicrobials for a periodontal abscess or acute necrotizing periodontal disease. Surprisingly, 31% of participants reported prescribing systemic antimicrobials for deep localized periodontal pockets or for acute gingivitis associated with herpes simplex in children. Noteworthy is that 66% of the participants thought that mechanical periodontal treatment alone, without adjunctive antimicrobial therapy, is adequate to resolve the clinical condition in most cases of periodontal diseases. Almost half of the participants recommended the use of local antimicrobials for a periodontal pocket (45.3%), a recurrent periodontal pocket (45.4%), and refractory periodontitis (43.7%). The barriers against the use of local antimicrobials were a lack of knowledge and a lack of continuous education after graduation, as reported by 64% of the participants. In conclusion, knowledge and practices regarding antimicrobial use for periodontal diseases were inadequate, especially among practitioners other than periodontists.